Integration of hydrogen energy systems into renewable energy systems for better design of 100% renewable energy communities - UYAR, TANAY SIDKI (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
This paper will introduce the concept of 100% renewable energy and the role hydrogen and fuel cells can play for storage and transportation sectors. The importance, necessity and possibility of an overall global transition from fossil and nuclear-based fuels to renewable energy fuels using electricity and hydrogen as clean energy carriers will be summarized. Polluted, inefficient and unhealthy societies of today are missing energy self-sufficient, better managed, in harmony with nature ecological communities. The possible role of hydrogen fuel cells in fulfilling this target will be demonstrated and the success stories of the leading countries will be given. Renewable energy investments which have started in 2013 increased steadily and reached to 290 billion dollars towards the end of 2015. Today's increasing investments and cheaper supply of renewable energy will in turn effect the hydrogen production costs and increase the diversion from fossil fuels to cheap renewable energy. This reality confirms that hydrogen energy technologies will play an important role in reaching the 100% renewable energy target. (C) 2016 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Climate change; Energy end use efficiency; Renewable energy; Planning the future energy mix; Smart grids; Storage